2021
DOI: 10.3390/polym13172999
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength and Low-Cost Biobased Polyurethane Foam Composites Enhanced by Poplar Wood Powder Liquefaction

Abstract: An environmentally friendly liquefaction of wood powder was prepared by atmospheric pressure liquefaction technology to replace the non-renewable petroleum polyols in the preparation of polyurethane foam composites. The liquefaction time varied from 0 min to 140 min. The composition of liquefied products and the effects of liquefaction time on the morphology, apparent density and mechanical properties of polyurethane foam composites were investigated. The results showed that the optimal process time for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As expected, the liquefaction reaction time has an influence on the mechanical properties of the resulting foams through the molecular weight of the obtained polyols. Recently, an intense variation of the polyol molecular weights with the liquefaction reaction time was observed [ 95 ]. The molecular weights of the polyols are dependent on the reaction parameters (time) ( Table 4 ).…”
Section: Applications Of Products Obtained By Biomass Liquefactionmentioning
confidence: 99%
“…As expected, the liquefaction reaction time has an influence on the mechanical properties of the resulting foams through the molecular weight of the obtained polyols. Recently, an intense variation of the polyol molecular weights with the liquefaction reaction time was observed [ 95 ]. The molecular weights of the polyols are dependent on the reaction parameters (time) ( Table 4 ).…”
Section: Applications Of Products Obtained By Biomass Liquefactionmentioning
confidence: 99%
“…Conventional polyurethane raw materials, such as polyether and polyester polyols, are petroleum-dependent products, which considerably limit their sustainable development [ 33 , 34 , 35 , 36 ]. The Earth’s crust contains over 90 elements, with O and Si accounting for approximately 49% and 26% of the total abundance of these elements, respectively [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was directly related to the use of a polyol derived from the liquefaction of lignocellulosic biomass, which presented a higher hydroxyl index than the one from the industrial polyol. In fact, authors contributing to the literature have already reported that higher values of the hydroxyl index usually lead to an incremented density of the polyurethane foams [ 77 , 78 ]. This is because a high hydroxyl number provides a higher degree of crosslinking of the PUF [ 79 ].…”
Section: Resultsmentioning
confidence: 99%